G489 Safe-tea: a parent targeted intervention to prevent hot drink scalds in pre-school children and improve first aid. (May 2019) - Bennett, CV; Hollen, L; Quinn-Scoggins, HD; Mytton, J; Nuttall, D; Emond, A; Kemp, AM
Abstract : Aims: Hot drink scalds in pre-school children account for a third of children's burns attendances in the ED and 43% of their parents have poor or little knowledge of burns first aid. Yet, there is a paucity of research into effective interventions to tackle these issues. We designed, developed and tested the feasibility of Safe-Tea, an innovative multi-faceted community-based intervention delivered by early-years practitioners. Methods: Safe-Tea was implemented at 19 childcare settings, 14 play groups (PGs) and 156 home visits (HVs), in urban areas of deprivation. A mixed methods approach was used, including pre- and post-intervention questionnaires and focus groups with parents and practitioners to test the acceptability, practicality, delivery and limited efficacy of Safe-Tea. Results: Intervention materials, activities and messages were well received and understood by both parents and practitioners. Interactive and visual methods of communication requiring little to no reading were most acceptable. Parents' knowledge of hot drink scald risks significantly (p<0.05) improved. Correct answers increased post-intervention to questions on: most at risk age (by 34% in PGs and 24% at HVs); mechanism (by 14% at HVs) and ease of skin damage (by 6% at HVs). Knowledge of correct first aid also increased significantly (p<0.05). Correct answers for burn cooling time increased by 43% (PGs) and 53% (HVs) and what to cover the burn with increased by 60% (PGs) and 52% (HVs). Parents reported improved understanding of the likelihood and severity of injury to children and increased vigilance around hot drinks. They gained confidence to correct the behaviours of others at home and pass on first aid messages. Conclusion: Safe-Tea is a feasible intervention that has the potential to reduce the incidence of hot drink scalds in pre-school children and improve the efficacy of parental first aid. This study is a vital step towards the development of a robust, evidence based behaviour change intervention model. Work is underway to refine intervention materials based on parent suggested improvements and test these more widely within the UK in preparation for a launch and evaluation of a national campaign in late 2019.